The problem with perceptions: an empirical investigation into the perception sixth formers have of 'politics' - Graham, Sarah (2016)
This dissertation details a case study empirical investigation into the perceptions a group of Sixth Formers had of ‘politics’ at one Nottinghamshire Sixth Form. The primary aim of this study is to use an investigation into Sixth Formers’ perceptions of ‘politics’ to gain an initial insight into their relationship with ‘politics’ in general. This insight can then inform future decisions as to how to improve pedagogical practice for the provision of political education at this Sixth Form. This aim is the result of a personal interest and a sense of professional duty, in light of the current British government’s mandated national Citizenship education programme, of which political education is a key component. This study selects a specific sub-category of young people termed ‘attainers’ as the focus of this investigation. ‘Attainers’ are defined, for the purposes of this study as, ‘young people eligible to vote for the first time’(Henn, Weinstein and Forrest,2005,p.1) and, as such, are defined primarily by their newly-acquired capacity to vote in UK General Elections. They are deemed a significant and interesting group to investigate when considering the role of this Sixth Form in providing effective political education for all students because they have just reached a significant and crucial watershed moment in their relationship with politics and as British Citizens. When investigating the perception my Sixth Formers have of ‘politics’, this study responds to three key issues. First, it establishes whether the prevalent perception in Britain today of young people as apathetic towards and disengaged towards ‘politics’ is accurate of my Sixth Form students. Second, if this prevalent perception is not accurate of my Sixth Form students, it establishes what exactly their perception of ‘politics’ is. Third, it compares the results of this empirical case study to the results of a pre-existing national study of the perceptions ‘attainers’ had of ‘politics’ across Britain carried out by Dr Matt Henn and Dr Nick Foard in 2011. This is in order to contextualise the case study results within a national picture, and to begin to gain an insight into key causal factors contributing to the relationship between young people and politics. Using this insight into the perceptions my Sixth Form students have of ‘politics’, this study concludes with suggestions for how I might go forward in my aim to improve pedagogical practice in the provision of political education for my Sixth Form students. It also offers tentative thoughts on the role perceptions play in the relationship between young people and politics, suggesting that one key area for improvement is to ensure that perceptions are always substantiated by sound empirical research.